Innovative approaches to promoting women's economic empowerment : paper for the partnership event on September 25, 2008 : MDG3 gender equality and empowerment of women : a prerequisite for achieving all MDGs by 2015. (UNDP, 2008)
Addressing the lack of progress on women's economic empowerment, this publication highlights approaches from all regions of the world, illustrating the range and combination of activities and ways in which these activities address and contribute to women's economic empowerment, and, more broadly, to the achievement of the MDGs. The publication focuses on three core dimensions: economic opportunity; legal status and rights; and voice, inclusion and participation in economic decision making.--Publisher's description.